2017
DOI: 10.3390/nu9050526
|View full text |Cite
|
Sign up to set email alerts
|

Urban–Rural Disparities in Energy Intake and Contribution of Fat and Animal Source Foods in Chinese Children Aged 4–17 Years

Abstract: Objective: Excessive energy intake and poor food choices are major health concerns associated with overweight and obesity risk. This study aims to explore disparities in energy intake and the contributions from fat and animal source foods among Chinese school-aged children and adolescents in different communities based on urbanization levels. Design: Three consecutive 24 h recalls were used to assess dietary intake. Subjects’ height and weight were measured using standard equipment. Standardized questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 37 publications
2
31
0
1
Order By: Relevance
“…association was expected in low and middle income countries and reinforces the work ofZhang et al (2017), who found that children from higher-income families consumed significantly higher proportion of animal sourced foods compared to children from lower-income families Christian et al (2012). offers a possible explanation for this finding as increased family income…”
supporting
confidence: 68%
“…association was expected in low and middle income countries and reinforces the work ofZhang et al (2017), who found that children from higher-income families consumed significantly higher proportion of animal sourced foods compared to children from lower-income families Christian et al (2012). offers a possible explanation for this finding as increased family income…”
supporting
confidence: 68%
“…Very limited information is available on dairy consumption in Chinese young children. Zhang et al [15] reported a lower consumption rate (14.8%) of milk and dairy products in rural Chinese children aged 4-17 years compared with those in highly (70.4%) and moderately (38.6%) urban areas in 2011, and daily energy contribution from dairy foods ranged from 6.0% to 7.8% on average. The findings in this study revealed the status of dairy food consumption and dietary nutrient intakes in Chinese children aged 3-8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Infancy and childhood are both critical periods of rapid physical growth and cognitive development [1]. At this stage of life, children have high nutrients needs; consequently, the right amount of dietary energy intake and the consumption of nutrient-rich foods are fundamental [2].…”
Section: Introductionmentioning
confidence: 99%